Public acceptance of using artificial intelligence-assisted weight management apps in high-income southeast Asian adults with overweight and obesity: a cross-sectional study - Chew, Han Shi Jocelyn; Achananuparp, Palakorn; Dalakoti, Mayank; Chew, Nicholas W. S.; Chin, Yip Han; Gao, Yujia; So, Bok Yan Jimmy; Shabbir, Asim; Peng, Lim Ee; Ngiam, Kee Yuan (Frontiers in Nutrition, 2024)
We aimed to examine user perceptions of artificial intelligence (AI)-based mobile apps for weight management in adults with overweight and obesity. 280 participants were recruited between May to November 2022. Participants completed a questionnaire on sociodemographic profiles, Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), and Self-Regulation of Eating Behaviour Questionnaire. Structural equation modeling was performed using R. Model fit was tested using maximum likelihood, generalised unweighted least squares.Associations between influencing factors were analysed using correlation and linear regression. 271 participant responses were analysed, representing participants with a mean age of 31.56 ± 10.75 years old, median (interquartile range) BMI, and waist circumference of 27.2 kg/m 2 (24.2-28.4 kg/m2) and 86.4 (80.0-94.0) cm respectively. 188 (69.4%) participants intended to use AI-assisted weight loss apps. UTAUT2 explained 63.3% of the variance in our sample's intention to use AI-assisted weight management apps with satisfactory model fit: CMIN/df=1.932, GFI=0.966, AGFI=0.954, NFI=0.909, CFI=0.954, RMSEA=0.059, SRMR=0.050. Only performance expectancy, hedonic motivation, and the habit of using AIassisted apps were significant predictors of intention. Comparison with existing literature revealed vast variabilities in the determinants of AI-and non-AI weight loss app acceptability in adults with and without overweight and obesity. UTAUT2 produced a good fit in explaining the acceptability of AI-assisted apps among a multi-ethnic, developed, southeast Asian sample with overweight and obesity. UTAUT2 model is recommended to guide the development of AI-assisted weight management apps among people with overweight and obesity.